Localized Bullous Pemphigoid in a Patient with Acquired Reactive Perforating Collagenosis - Masahiro Oka (Karger Publishers, 2023)
A 61-year-old man presented with 6-month and 5-day histories of multiple, pruritic nodular eruptions on the trunk and extremities and bullous eruptions on the left foot, respectively. The nodular eruptions had been treated with topical corticosteroids without improvement. He had been diagnosed with diabetes mellitus at the age of 42 years and had been suffering from end-stage renal disease for 1 year. Physical examination revealed scattered violet-brown papules and nodules on the trunk and extremities, many of which had central umbilicated necrosis or keratin plugs. Additionally, two tense bullae and five erosions were noted on the dorsal aspect of the left foot. Laboratory tests showed elevated levels of serum anti-bullous pemphigoid (BP)180 antibody. Histopathological findings of a nodule and a bulla were compatible with those of acquired reactive perforating collagenosis (ARPC) and BP, respectively. The papular and nodular lesions were diagnosed as ARPC, while bullous and erosive lesions were diagnosed as localized BP. The present case, together with previously reported cases of coexisting generalized BP and ARPC, suggests that coexistence of BP, regardless of whether generalized or localized, is significantly associated with ARPC.